The Identification of Gastropods in Seagrass Ecosystem of Madong Village, Kampung Bugis Village, Tanjungpinang Kota District, Kepulauan Riau Province - Pratiwi, Nadia Indah; Eddiwan, Eddiwan; Efawani, Efawani (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
Abstract Madong Village is one of the coastal areas that is overgrown by vegetation in the form of seagrass which is a habitat for marine life, among other is gastropods. The presence of community activities around the seagrass ecosystem might affect the quality of waters and organisms associated with the ecosystem, especially gastropods. Information about the species of gastropods in the region is still limited. To find out the species of gastropods in the seagrass ecosystem of Madong Village, this research was conducted in March-April 2019. There are 3 research stations, and each station has 3 line transects with 1x1 m quadrat. The results shown that the gastropods found consisted of 5 families and 6 species, which are: Cerithium coralium, Cerithidea cingulata, Strombus canarium, Strombus urceus, Pyrene scripta, and Nassarius crematus. The conditions of the water quality obtained ware temperature ranges from 30-32º C, current speed 0.15 m/sec, dissolved oxygen 6.7-6.9 mg/L, acidity (pH) 8, salinity 31-35 ‰. The type of substrate at Station I and II is muddy sand, while Station III is sandy mud. Keywords: Madong Village, seagrass ecosystems, gastropods species,Cerithium coralium, Strombus urceus.